Physicochemical characteristics of seeds from wild and cultivated castor bean plants (Ricinus communis L.) (2018)
The castor (Ricinus communis L.) is an oilseed plant whose main features are its drought resistance, and its adaptation to eroded, polluted, and low fertility soils. Its oil has a great demand in the industrial sector and it has recently attracted considerable interest for its use in the production of biodiesel and jet fuel. In this study, morphological, physical and chemical characterizations were performed to ascertain the quality of wild (VQ-1) and under cultivation (VQ-7) oil castor seeds. The results showed that there are differences in the morphological and physicochemical characteristics regarding oil content (44,95 vs 33,84%), ash (3,20 vs 2,42%), and 100-seed-weight (45,87 vs 54,23g); similar behavior was recorded when characterizing the oil: kinematic viscosity (269,67 vs 266,44mm2 /s), density (0,9389 vs 0,9465g/cm3 ), and acidity index (0,9918 vs 0,5440mg KOH/g) for VQ-1 and VQ-7, respectively. Growing conditions to which castor plants were subjected may influence both the final quality of seeds and chemical properties of the oil.